Guggulsterone Suppresses Ovalbumin- Induced Inflammation in Rat Asthmatic Model - Zainab H. Ahmed1 , Munaf H. Zalzala2, Manal A. Ibrahim1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Asthma is an inflammatory airway disease, which is characteristic by wheezing, chesttightness, dyspnea and cough, all symptoms that are occupied with obstruction of respiratory airway. Aim:investigate guggulsterone activity on improve inflammatory events that associated with asthma. Method:48 healthy rats (albino, male) divided to 6 groups, rats were sensitized with OVA and preparation lung tissuehomogenate for measurement of inflammatory parameters by ELISA and RT-PCR. Also, preparation of lungtissue for histopathological examination. Results: All parameters are significant reduction in treated groupwith guggulsterone than sensitized group. Also, gugglsterone-treated group’s slides with less inflammatorysigns compared to sensitized group slide. Conclusion: Guggulsterone improve inflammatory events thatassociated with asthma.